2021
DOI: 10.1111/pbi.13569
|View full text |Cite
|
Sign up to set email alerts
|

Identification of rice (Oryza sativa L.) genes involved in sheath blight resistance via a genome‐wide association study

Abstract: Rice sheath blight (RSB) is an economically significant disease affecting rice yield worldwide. Genetic resistance to RSB is associated with multiple minor genes, with each providing a minor phenotypic effect, but the underlying dominant resistance genes remain unknown. A genomewide association study (GWAS) of 259 diverse rice varieties, with genotypes based on a single nucleotide polymorphism (SNP) and haplotype, was conducted to assess their sheath blight reactions at three developmental stages (seedlings, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…The multi-protein complex then modulated GmSHMT08 activity in maintaining the intracellular redox homeostasis in resistance to soybean cyst nematodes (SCN) ( Lakhssassi et al, 2020 ). In rice, OsSHM1 participated in sheath blight resistance via a similar mechanism in soybean ( Wang et al, 2021 ). In addition, a tomato SHMT protein regulated salicylic acid (SA) signaling-dependent basal defense against Pseudomonas syringae ( Ahammed et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The multi-protein complex then modulated GmSHMT08 activity in maintaining the intracellular redox homeostasis in resistance to soybean cyst nematodes (SCN) ( Lakhssassi et al, 2020 ). In rice, OsSHM1 participated in sheath blight resistance via a similar mechanism in soybean ( Wang et al, 2021 ). In addition, a tomato SHMT protein regulated salicylic acid (SA) signaling-dependent basal defense against Pseudomonas syringae ( Ahammed et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…OsWRKY62 , a negative rice disease resistance regulator (J. Liu et al, 2016a; Peng et al, 2008), always maintained a higher transcription level in the osscl7–1 mutant than in the wild type before and after M. oryzae inoculation. OsWRKY89 , a positive rice resistance regulator (A. Wang et al, 2021a; H. Wang et al, 2007), was significantly downregulated in the osscl7–1 mutant compared to the wild type after M. oryzae inoculation. Taken together, these results indicated that OsSCL7 was involved in the regulation of a series of plant defence‐related genes, such as PR genes, PAL genes and transcription factor genes.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, guanine activated jasmonic acid and ethylene signaling pathways to protect plants against pathogens. The mechanism of rice resistance to ShB is still largely unknown, and ShB control relies heavily on chemical fungicides ( Zheng et al, 2013 ; Li et al, 2019 ; Wang et al, 2021 ). In this study, 100 ng/mL guanine significantly enhanced rice resistance to ShB, providing a novel, green and efficient strategy for ShB prevention and control.…”
Section: Discussionmentioning
confidence: 99%